2022
DOI: 10.1111/jhn.12987
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary factors and body weight and composition in boys with Duchenne muscular dystrophy

Abstract: Background: Duchenne muscular dystrophy (DMD) is a X-linked neuromuscular disorder. Boys with DMD have high rates of obesity, although little is known about dietary factors that may contribute to weight gain in this population. The present study aimed to explore the relationship between dietary factors, body mass index (BMI) z-score, body composition and motor function and to describe dietary intake in boys with DMD. Methods: A cross-sectional analysis of 3-day food diaries from ambulant and steroid treated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The importance of preventable interventions on weight management such as dietary optimization should not be underestimated. Previous studies have observed mismatches in caloric intake being excessive in pre‐school and school‐age groups 14,23 . Greater emphasis on weight‐related strategies and regular nutrition counseling early in the disease course should be at the forefront of bone health in boys with DMD 6,23 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The importance of preventable interventions on weight management such as dietary optimization should not be underestimated. Previous studies have observed mismatches in caloric intake being excessive in pre‐school and school‐age groups 14,23 . Greater emphasis on weight‐related strategies and regular nutrition counseling early in the disease course should be at the forefront of bone health in boys with DMD 6,23 .…”
Section: Discussionmentioning
confidence: 98%
“…21 Mechanisms of how higher BMI can correlate with fracture rates, particularly lower limb fractures may include inappropriate adaptation of the axial skeleton with body size and impaired balance. 11,23 Unique to dystrophin deficiency, boys with DMD also exhibit progressive replacement of lean muscle mass with intramuscular adipose tissue; both reducing energy expenditure, increasing body fat mass, and impacting the structural integrity of the axial skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 In two prior investigations of dietary intake of individuals with DMD, higher total energy intakes compared to estimated requirements and displacement of core food groups with discretionary (non-core) foods were observed. 15,16 Qualitative research has identified challenges associated with weight management such as competing health care priorities, the complexities of the high level of care needs that comes with DMD, and balancing dietary restriction and the enjoyment associated with food. 17,18 This study aimed to extend existing knowledge by exploring specific barriers and enablers that influence nutritionand weight-related behaviors as well as attitudes and beliefs about nutrition and weight management in the home environment.…”
Section: Introductionmentioning
confidence: 99%